Factors Affecting the Profitability of Islamic Commercial Banks in Indonesia from 2015 to 2019 - Suhendi; Ahmad Fadlan; Sri Wahyuni (Best Journal of Administration and Management, 2024)
Profitability of Islamic commercial banks in Indonesia is one of the important aspects in assessing the performance and sustainability of sharia-based financial institutions. One of the indicators used to measure the level of profitability is Return On Asset (ROA). ROA is the ratio between profit after tax to total assets. This ratio reflects the ability of bank management to use its investment resources to increase revenue. This study was conducted to analyze the factors affecting the profitability of Islamic Commercial Banks in Indonesia from 2015 to 2019. The research sample consists of quarterly data on economic growth and inflation from 2015 to 2019, as well as quarterly financial reports from 11 Islamic Commercial Banks in Indonesia that meet the criteria for complete annual financial reports during the period of 2015-2019, totaling 220 data points. The analytical technique used to interpret and analyze the data in this study is the Generalized Least Squares (GLS) panel data regression, operated using Eviews 9.0 software. In a partial analysis, the capital variable has a positive and significant effect on the profitability variable. The liquidity variable has a positive and significant effect on the profitability variable. The bank size variable has a positive and significant effect on the profitability variable. The inflation variable has a positive but not significant effect on the profitability variable. The economic growth variable has a positive and significant effect on the profitability variable.